England’s Lost Renaissance? Anglo-Venetian politics between the household of Prince Henry and the court of James VI & I - Davies, E (Taylor and Francis, 2022)
This article traces an intellectual and religious network that connected the circles of King James VI and I and his son, Henry, prince of Wales. Henry — who died aged only eighteen — has often been presented as a lost Protestant hero, whose anti-papal militarism radically differed from James’s conciliatory pro-Spanish stance. Concentrating on James and Henry’s relations with Venice, this article draws on documents from England and Italy to demonstrate that the ideals and aspirations of the court circles of the royal father and son were not as different as traditionally thought. Through close engagement with Venetian art and political culture, Henry and his household helped to support and further — rather than undermine — James’s foreign policy. This fresh analysis of James and Henry’s circles offers a new perspective on the role of the Harington family as major players in Jacobean politics. It also sheds light on the significant role of clergymen in court life.